Influência do controle virológico e da terapia antirretroviral no balanço autonômico cardiovascular em sujeitos com HIV - Casarin, Naiára (2017)
The use of antiretroviral therapy (ART) in Human Immunodeficiency Virus (HIV) is associated with the increase of risks of developing cardiovascular disease. The autonomic dysfunction is reported and consequently resulting in sympathetic and parasympathetic imbalance and morbi-mortality growth. The objective of this study was to evaluate the effects of ART and virological control regarding autonomic balance and cardiovascular risks on HIV people. Sixty HIV patients were evaluated from the Infectious Diseases Clinic AT University Hospital of Santa Maria (HUSM) and Casa Treze of Maio Clinic at Santa Maria/RS, subdivided in three groups: ART and undetectable viral load (GTCV-; n=20); ART and detectable viral load (GTCV+; n=20); and without ART and detectable viral load (GsTCV+; n=20). The autonomic cardiovascular control was calculated taking into consideration the heart rate variability (HRV) in the control of time and frequency with a Polar heart rate monitor watch model 810i. The registers acquired in controlled respiration (12 breaths a minute; relation I:E=1/3) were used, during 10 minutes. The Framingham Risk Score was employed in order to evaluate the risks of cardiovascular events. The results demonstrate the groups did not differ regarding gender, age and body mass index. The viral load was smaller in GTCV+ rather than GsTCV+. The T-CD4 numeration was bigger in GTCV- rather than others. In the HRV analysis, the heart rate (HR) was bigger in GsTCV+ (77,6±12,7 bpm) than GTCV- (66,2±11,9 bpm; p<0,01). The Framingham Risk Score and probability of cardiovascular risks did not differ among the groups. It is concluded that the use of ART and a better virological control reduce the HR response, which suggests a reduction of cardiac work in repose and it is able of deflecting in better clinic outcomes concerning HIV patients.